Berberine Reduces Aβ42 Deposition and Tau Hyperphosphorylation via Ameliorating Endoplasmic Reticulum Stress - Wu, Yue; Chen, Qingjie; Wen, Bing; Wu, Ninghua; He, Benhong; Chen, Juan (Frontiers in Pharmacology, 2021)
Alzheimer’s disease (AD) is tightly related to endoplasmic reticulum stress (ER stress), which aggravates two dominant pathological manifestations of AD: senile plaques and neurofibrillary tangles. Berberine is widely applied in the clinical treatment of many diseases and is reported to have anti-AD effects. In the present study, berberine was shown to ameliorate ER stress and cognitive impairment in APP/PS1 mice. We found ER stress plays a role as central hub for signal transduction which was evidenced by the hyperactivation of glycogen synthase kinase 3β (GSK3β) to phosphorylate tau, activation of PRKR-like endoplasmic reticulum kinase (PERK) subsequently to phosphorylate eukaryotic translation initiation factor-2 α (eIF2α). Also eIF2α has regulated the expression of beta-site APP cleaving enzyme-1 (BACE1), which cleaves APP into pro-oligomerized amyloid beta 42 (Aβ42), the main component of senile plaques, proven by using siRNA targeting at eIF2α. Mechanically, berberine can reduce GSK3β activity, contributing to the downregulation of tau phosphorylation. Berberine also suppressed Aβ42 production via inhibiting PERK/eIF2α/BACE1 signaling pathway. Taken together, these findings indicated that berberine had the potential to ameliorate two major pathological manifestations of AD mainly by suppressing ER stress. Our work provided knowledge on the pharmacological intervention of AD and the possible targets for future drug development.